IMPLEMENTASI STRATEGI MARKETING MIX 7P PADA PRODUK iB HIJRAH HAJI (STUDI BANK MUAMALAT KCP BONE) - Sari, Novita (Faculty of Islamic Economics and Business, 2023)
To continue to exist and be able to compete with conventional banks, marketing strategies from Islamic banks are needed that can be welcomed and enthusiastically received by the public. In marketing science, known as the0concept0of0the0marketing0mix0for market penetration steps, marketing products to the market requires several strategies which include several 7 elements consisting of:0product,0price,0place and0promotion,0people,0physical0evidence0and0process. Bank Muamalat, as the first sharia bank in Indonesia that was able to survive during the monetary crisis, is one of the Recipient Banks for Hajj Pilgrimage Deposits (BPS-BPIH) registered at the SISKOHAT Ministry of Religion of the Republic of Indonesia. This study0aim0to0determine0how implementation the marketing mix 7P strategy of iB Hijrah Hajj in Muamalat Bank Sub Branch of Bone. This0type0of0research0is field0research using qualitative0research0methods0and0escriptive approach. that is collected0through observation, interview and0documentation techniques which are then processed and analyzed with the methods0of data reduction, data presentation0and drawing conclusions. The Marketing Mix 7P strategy at Muamalat KCP Bone bank has been implemented properly, starting from Product: more practical, comfortable, lightweight, seems popular and easy to remember with the word